2018
DOI: 10.1002/clen.201800077
|View full text |Cite
|
Sign up to set email alerts
|

Abatement of Amoxicillin, Ampicillin, and Chloramphenicol From Aqueous Solutions Using Activated Carbon Prepared From Grape Slurry

Abstract: The adsorption of amoxicillin (AMX), ampicillin (AMP), and chloramphenicol (CHLR) from simulated antibiotic‐contaminated water using adsorbents prepared from grape slurry waste is studied. Batch adsorption experiments are carried out to evaluate the adsorption capacity of the adsorbents for AMX, AMP, and CHLR. Adsorption isotherms are described by the Langmuir and Freundlich isotherms, while the pseudo‐second order kinetics describe the sorption processes. Negative values of the enthalpy change show that the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 74 publications
0
22
0
Order By: Relevance
“…Both sets of Qe values are somewhat in agreement with the experimental values, 39.92mg/g (MO) and 42.87 mg/g (AMX), however, the pseudo first order values are closer. Pseudo firs order kinetics describes a physiosorptive processes involving non-bonding forces (Chitongo et al, 2019). This may have also contributed to the adsorption process for both MO and AMX, as shown…”
Section: Resultsmentioning
confidence: 92%
“…Both sets of Qe values are somewhat in agreement with the experimental values, 39.92mg/g (MO) and 42.87 mg/g (AMX), however, the pseudo first order values are closer. Pseudo firs order kinetics describes a physiosorptive processes involving non-bonding forces (Chitongo et al, 2019). This may have also contributed to the adsorption process for both MO and AMX, as shown…”
Section: Resultsmentioning
confidence: 92%
“…In addition, the adsorption of ampicillin was declined at pH values higher than 7. The formation of electrostatic repulsion forces between carboxylate groups present in ampicillin molecules and the negative surface charges of the ACAF could describe the observed event in these pH values [ 39 ]. Moreover, it is expected that π-π interaction between a benzene ring of ampicillin and ACAF happens, which leads to the developing of adsorption capacity [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…103 A study on the removal of chloramphenicol from contaminated water using adsorbents made from grape slurry waste has been reported. 104 A batch experiment was carried out using simulated antibiotic-contaminated water. According to the study, waste grape slurry could be a useful starting point for creating efficient adsorbents for treating wastewater polluted with antibiotics.…”
Section: Agricultural Biomass-based Adsorbents For Antibiotics Removalmentioning
confidence: 99%
“…Thermodynamic analyses also revealed that the sorption of CHLR was an exothermic reaction that was conceivable but not spontaneous as the temperature rose. 104 The adsorptive removal of antibiotic contaminants from wastewater using biochar from peanut shells was studied. 105 In this study, chloramphenicol served as the reference antibiotic.…”
Section: Agricultural Biomass-based Adsorbents For Antibiotics Removalmentioning
confidence: 99%
See 1 more Smart Citation